The Power of New Online Opportunities to Connect to the Ocean: The Journey of a Research Student and Mentor. Issue 3 (18th December 2020) - Guertin, Laura; Briseño, Isabella
This commentary shares a unique collaborative experience between a student and faculty mentor, made possible by the shift from in-person to virtual conferences during summer 2020. Although the two never met face-to-face, online technologies made it possible to facilitate the mentoring, project development, and dissemination of ArcGIS StoryMaps themed on ocean literacy, the United Nations Sustainable Development Goals, and United Nations Decade of Ocean Science for Sustainable Development. The StoryMap collection is available at:https://bit.ly/thepowerofconnections .